Wave Retail Banking Effect on Customer Satisfaction in Retail Supply Chain in Bangladesh - Mahadi Hasan Miraz; A. K. Mahbubul Hye; Md. Mamun Habib (International Journal of Supply Chain Management, 2020)
Abstract-Purpose: The purpose of this study is a clarification of changes of supply chain management (SCM) in public organizations and the nature of change management (CM). The paper also examines and demonstrate the trust influencing CM in technology adoption in Bangladesh pubic organizations. The aim of this paper is, consequently, to identify precarious success factors for CM. Theory: In this study we focus on the adoption of technology such as the Technology Acceptance Model (TAM), highlighted the need to broaden the scope of theoretical mechanisms. Method: In this study, we obtained the empirical data necessary to validate the theoretical framework. In total of 460 self-administered questionnaires were used to derive public sector responses in Bangladesh in their perceptions of trust and aspects of change management. Originality: This study an outline of CM in TA projects is recognized based on the literature review and empirical evidence. Significance: This study will enhance the service and management of public organization. Besides that, it will provide quality service for public organization. Finally, it will introduce technology supply chain in organization management. Outline: the paper concludes with a presentation of the study’s, framework and contributions as well as the stream of upcoming research.